2020
DOI: 10.5604/01.3001.0013.9781
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Lateral Ankle Instability: Results of Anatomic Repair with Polyester Tape Augmentation

Abstract: Background. Ankle sprains are one of the most common injuries in both athletes and the general population. A major problem accompanying ankle injury is the high rate of recurrence, with about 20% of acute ankle sprain patients developing chronic ankle instability. Unlike acute ankle sprain, chronic ankle instability usually needs surgical intervention. Various anatomic reconstruction techniques using the ruptured ends of the ligaments to restore stability have gained popularity. The purpose of this study was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The most frequently cited category of spin was type 3 (“selective reporting or overemphasis on efficacy outcomes or analysis favoring the beneficial effect of the experimental intervention”) (6 of 19, 31.6%). Sarhan et al 31 presents an example of type 3 spin by claiming that “ankle ligament reconstruction with addition of polyester tape augmentation is an effective technique in treating chronic ankle instability with satisfactory surgical outcome” using only the American Orthopaedic Foot & Ankle Society (AOFAS) and free online Foot and Ankle Ability Measure (FAAM) scores in their analysis. Only the AOFAS score demonstrated a significant improvement compared to the preoperative scores, whereas the actually validated FAAM score change was insignificant.…”
Section: Discussionmentioning
confidence: 99%
“…The most frequently cited category of spin was type 3 (“selective reporting or overemphasis on efficacy outcomes or analysis favoring the beneficial effect of the experimental intervention”) (6 of 19, 31.6%). Sarhan et al 31 presents an example of type 3 spin by claiming that “ankle ligament reconstruction with addition of polyester tape augmentation is an effective technique in treating chronic ankle instability with satisfactory surgical outcome” using only the American Orthopaedic Foot & Ankle Society (AOFAS) and free online Foot and Ankle Ability Measure (FAAM) scores in their analysis. Only the AOFAS score demonstrated a significant improvement compared to the preoperative scores, whereas the actually validated FAAM score change was insignificant.…”
Section: Discussionmentioning
confidence: 99%
“…found that polyester tape augmentation improved American Orthopaedic Foot and Ankle Society (AOFAS) and FAAM median scores in patients with lateral ankle instability. 33 Xu et al. compared a modified Broström repair with and without augmentation using suture tape and found that patients with suture tape augmentation had significantly improved total outcome scores compared to the group without suture tape augmentation.…”
Section: Discussionmentioning
confidence: 99%
“…Open Brostro ¨m repair with suture tape augmentation (BR-ST) 13,17,22,23,26,49,51,52,65,70,85 Modified or traditional open Brostro ¨m repair with knotless suture anchors augmented with nonabsorbable polyethylene/polyester suture tape used as secondary stabilizer to ATFL Ligament augmentation reconstruction system (LARS) 63,64 Synthetic ligament with ATFL and CFL limbs placed in extra-articular location to augment primary repair of LCL complex Arthroscopic Brostro ¨m repair with suture tape augmentation (ABR-ST) 24,79,88 Modified or traditional arthroscopic Brostro ¨m repair with knotless suture anchors augmented with non-absorbable polyethylene/polyester suture tape used as secondary stabilizer to ATFL Suture tape augmentation only (STO) 12,15,16,76 Percutaneous or minimally invasive approach to reinforce ATFL and/or CFL without concomitant Brostro ¨m repair Abbreviations: ATFL, anterior talofibular ligament; CFL, calcaneofibular ligament; LCL, lateral collateral ligament.…”
Section: Technique Overviewmentioning
confidence: 99%